Epitaxial growth of semi-polar (11-22) gallium nitride FOR UV photosensing application / Abdullah Haaziq Ahmad Makinudin - Abdullah Haaziq , Ahmad Makinudin (2020)
Semi-polar (11-22) gallium nitride (GaN) epilayers have attracted numerous interests in GaN based technology as it possess significant advantages over its polar (c-plane) counterparts such as low to none spontaneous and piezoelectric polarization which is known to impair the device performance. However, growth along semi-polar (11-22) orientation has been known to exhibit numerous defect densities such as dislocations and stacking faults (SFs). In order to acquire high quality semi-polar (11-22) GaN epilayers, various growth optimizations must be employed. In this work, the semi-polar (11-22) GaN epilayers were grown on planar m-plane sapphire substrate with the use of a 2-inch capability horizontal metal organic chemical vapor deposition (MOCVD). This work is divided into three main phases namely phase I, where the optimization of the unintentionally-doped GaN epilayer was conducted with variations of three key parameters which includes the nitridation procedure, the V/III ratio of the Uid-GaN epilayer as well as the insertion and variation of the V/III ratio of the aluminum nitride (AlN) nucleation layer. The V/III ratios of the Uid-GaN were optimized via the variation of the ammonia (NH3) flux from 0.4 to 1.0 standard liter per minute (slm) whilst the V/III ratios of the AlN nucleation layer were conducted through the variation of the aluminum (Al) source, trimethylaluminum (TMA) from 50 to 98.5 standard cubic centimeters (sccm). Upon attaining the desired quality of the subsequent Uid-GaN epilayer, implementation of three in-situ defect reduction technique was conducted in phase II of the work namely, (i) insertion of single NH3 treatment with constant NH3 flux of 1 slm at different duration of 90-360 seconds, (ii) multiple NH3 treatment with NH3 flux of 1 slm and different number of alternations and (iii) inter-multilayers of AlN and GaN with different pairing numbers from 20-200 pairs prior to the growth of the subsequent Uid-GaN epilayer. The final stage of the work is Phase III where optimization of the final structure of the device is optimized prior to the ultraviolet (UV)-photodetector device performance evaluation. Additional transition layer consists of a thin n-GaN epilayer was grown on the Uid-GaN epilayer of higher and lower qualities prior to a thin Uid-GaN layer was realized for the device structure. Symmetric nickel (Ni) contact electrodes for the metal-semiconductor-metal device structure were further deposited via an electron beam deposition prior to the device performance analysis. The crystal qualities of the epilayers were then analyzed via a high resolution x-ray diffraction (HR-XRD) through a phase analysis, on- and off-axis x-ray rocking curve (XRC) analysis and reciprocal space mapping (RSM). Morphological analysis was conducted via a field emission scanning electron microscope (FESEM) and an atomic force microscope (AFM). Electrical properties were analyzed via Hall-effect measurement and the in depth defect analysis were analyzed via a transmission electron microscope (TEM). The device performance on the other hand was analyzed via a photodetection measurement with the use of Keithley 236 Source Measure Unit equipped with an Oriel (Xenon arc lamp) solar simulator.